Massive cardiopulmonary cement embolism with cardiac perforation after vertebroplasty: a case series. Issue 9 (15th September 2022) - Schoechlin, Simon; Schröfel, Holger; Czerny, Martin; Siepe, Matthias; Ahlgrim, Christoph; Zeller, Thomas; Neumann, Franz-Josef
Abstract: Background: The prevalence of cement embolism after percutaneous vertebroplasty ranges from 2.1 to 26%, in literature. Even if most cases remain asymptomatic, intracardiac cement embolism becomes symptomatic in up to 8.3% of the cases. Case summary: We report a case series of two cases with massive cardiopulmonary cement embolism, which lead to perforation of the right ventricle and needed cardiothoracic surgery. Discussion: As this entity affects different fields of medical specialties and may lead to fatal outcome, we believe that the efforts of better understanding its development, avoidance, detection, and treatment need to be intensified. For this purpose, systematic and interdisciplinary studies to follow up patients after vertebroplasty are needed.